Photophysical effects on laser induced grating spectroscopy of toluene and acetone - Williams, B; Ewart, P (2012)
The modulation depth of signals in laser induced grating spectroscopy arising from the interplay of acoustic and stationary gratings is shown to be an indicator of the quenching dynamics in toluene and acetone vapours. The variation of this parameter with partial pressure of the primary quenching species, oxygen, and with total pressure in the range 1-8 bar of oxygen/nitrogen mixtures is reported. Differences in the variation of modulation depth with oxygen concentration and with total pressure between acetone and toluene are explained using a model of the photo-physics and internal molecular relaxation mechanisms. © 2012 Elsevier B.V. All rights reserved.